Attachment networks in young adults - Carli, Lucia L.; Alì, Paolo Alessandro; Anzelmo, Elena; Caprin, Claudia; Crippa, Franca; Gallucci, Marcello; Moioli, Loredana; Traficante, Daniela; Feeney, Judith A. (Frontiers in Psychology, 2024)
This study investigated attachment networks in a sample of Italian young adults. Attachment networks were defined in terms of attachment functions, attachment strength, the presence of a primary figure, and full-blown attachments. Participants were 405 young adults, and we studied the effects of the demographic variables of gender, romantic status (whether single, involved in a romantic relationship for less or more than 24 months) and employment (whether university students or workers) on the structure of attachment networks. Results indicated that while friends still had great importance in the network, partners were acquiring increasing relevance; at the same time, parents, and particularly mothers, remained central figures, particularly for the secure base function. Regarding the demographic variables, we observed that women reported stronger bonds with their mothers than men did, while the importance of friends was higher for men than for women. Additionally, our study supports previous findings underlining the importance of romantic partners in this phase of life, with participants involved in romantic relationships for longer than 24 months showing a fully developed attachment bond with their partners. Finally, for workers, the transfer of functions from the family-of-origin to external figures seemed to be fostered. In conclusion, young Italian young adults go through a phase of intensive restructuring of attachment bond networks, particularly in relation to the consolidation of romantic relationships and work commitments.